The Effect of Online Learning During the Covid-19 Pandemic on Student's Learning Motivation at University Buana Perjuangan Karawang - Zenita Apriani (International Journal of Ecma Science, 2021)
This study aims to explain in detail how the objective conditions of motivation experienced by students in online learning during the period Covid-19 pandemic. This study uses a quantitative approach using survey methods. This research was conducted at the University of Buana Perjuangan Karawang involving 50 students in the Economics and Business study. Data collection in this study used a survey technique with a Likert scale. The survey is made in a google form so that it can be easily accessed by students. The data analysis technique used is to calculate the percentage of data from each indicator, then interpret the percentage score and analyze each indicator in depth. Based on the results of the analysis of student motivation towards online learning during covid-19 pandemic average score the overall percentage is 50%, with sufficient category. so that it can be interpreted that UBP Karawang students lack the motivation to learn online during the pandemic Covid-19. Has sufficient limitations such as sufficient concentration, poor curiosity, and sufficient enthusiasm for learning. Such as media, materials, application usage, network access and quotas are obstacles for students in online lectures. This research is expected to be an evaluation of various parties in conducting online learning in universities, especially those involving motivation in it, this research is also expected to be a study material for other researchers in analyzing and developing students' learning motivation in online learning during an emergency in higher education.